Effect of Metallic Microfiber Flow Through Diesel Particulate Filter System on Diesel Engine’s Particle Emission Physicochemical Characteristics - Oh, Ban seok; Thaeviriyakul, Poonnut; Phairote, Watanyoo; Srilomsak, Mek; Charoenphonphanich, Chinda; Po-ngaen, Watcharin; Srimanosaowapak, Sompong; Hanamura, Katsunori; Karin, Preechar (My University, 2023)
It is well known that particulate matter (PM) from diesel compression ignition engines is harmful to the environment and to human health. To reduce engine PM emissions, exhaust after-treatment systems are utilized. A basic high-performance system can be composed of a diesel oxidation catalyst (DOC) and diesel particulate filter (DPF). This study used a system composed of a DOC and a partial flow DPF. Partial flow refers to how only a portion of the exhaust gas is filtered using metal fibrous filters instead of the full flow using ceramic filters. The PM deposited on the side wall of the stages of the system was investigated with respect to elemental composition, morphology, and nanostructure. This was to determine the effect of each component on the PM. The elemental composition analysis found traces of the engine lubricant oil in the PM collected before entering the DOC. This was then eliminated by the DOC and the remaining PM was not significantly impacted by the exhaust after-treatment system. The morphology and nanostructure show an interesting relationship where the size of the single primary particles increased while the graphitic nature of the carbon in the PM seemed to decrease. This can be explained by the simultaneous nature of partial trapping and partial oxidation that occurs in the partial-flow DPF. The emission measurements of opacity, temperature, CO2, NO, and O2 from each position also support this.
Keywords: Carbon nanostructure; Diesel emissions; Exhaust after-treatment; P-DPF; PM; Soot